PENGARUH KARAKTERISTIK KOMITE AUDIT, FEE AUDIT, UKURAN KAP, DAN INTERNAL AUDITOR TERHADAP KETEPATAN WAKTU (TIMELINESS) PELAPORAN KEUAGAN (Studi Empiris Pada Perusahaan yang Listing di BEI tahun 2013) - Bunga Pramudia Putri; Kennedy -; Yuneita Anisma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to examine the effect of audit committee characteristics, audit Fees, Public Accountant’s Size, and the existence of internal auditor toward timeliness. Characteristic of audit committee can be seen from size of audit committee, frequency of audit committee meeting, and financial expertise of audit committee. The population in this study is all firms listed in Indonesia Stock Exchange periode 2013. Sample of this research is 80 firms listed in Indonesia Stock Exchange periode 2013 that selected by using purposive sampling method. Data analysis using logistic regression at levels significance 5%. The result showed that the number of financial expertise on the audit committee, Public Accountnt’s size, and the existence of internal auditor significantly affect timeliness of financial reporting of the firm, while variable the size of audit committee, frequency of audit committee meeting, Audit Fees not have an affect to timeliness of financial reporting of the firm listed in Indonesia Stock Exchange 2013.Keywords: Timeliness, auditor,audit fees, and financial statement